Comprehensive Analysis of Long Non-coding RNA Modulates Axillary Bud Development in Tobacco (Nicotiana tabacum L.) - Wang, Lin; Gao, Junping; Wang, Chen; Xu, Yalong; Li, Xiaoxu; Yang, Jun; Chen, Kai; Kang, Yile; Wang, Yaofu; Cao, Peijian; Xie, Xiaodong (Frontiers in Plant Science, 2022)
Long non-coding RNAs (lncRNAs) regulate gene expression and are crucial for plant growth and development. However, the mechanisms underlying the effects of activated lncRNAs on axillary bud development remain largely unknown. By lncRNA transcriptomes of axillary buds in topped and untopped tobacco plants, we identified a total of 13,694 lncRNAs. LncRNA analysis indicated that the promoted growth of axillary bud by topping might be partially ascribed to the genes related to hormone signal transduction and glycometabolism, trans-regulated by differentially expressed lncRNAs, such as MSTRG.52498.1, MSTRG.60026.1, MSTRG.17770.1, and MSTRG.32431.1. Metabolite profiling indicated that auxin, abscisic acid and gibberellin were decreased in axillary buds of topped tobacco lines, while cytokinin was increased, consistent with the expression levels of related lncRNAs. MSTRG.52498.1, MSTRG.60026.1, MSTRG.17770.1, and MSTRG.32431.1 were shown to be influenced by hormones and sucrose treatments, and were associated with changes of axillary bud growth in the overexpression of NtCCD8 plants (with reduced axillary buds) and RNA interference of NtTB1 plants (with increased axillary buds). Moreover, MSTRG.28151.1 was identified as the antisense lncRNA of NtTB1. Silencing of MSTRG.28151.1 in tobacco significantly attenuated the expression of NtTB1 and resulted in larger axillary buds, suggesting the vital function of MSTRG.28151.1 axillary bud developmen by NtTB1. Our findings shed light on lncRNA-mRNA interactions and their functional roles in axillary bud growth, which would improve our understanding of lncRNAs as important regulators of axillary bud development and plant architecture.